Synthesis and Determination of Al3+ in Chinese Herbs from Heilongjiang Province by Fluorescent Probe of Naphthalimide - Guang YANG; Yan LANG (Medžiagotyra, 2023)
We reported a new naphthalimide fluorescence probe M1[dimethyl 3, 3'-((2-((2-butyl-1, 3-dioxo-2, 3-dihydro-1H-benzo[de] isoquinolin-6-yl) amino) ethyl) azanediyl) dipropionate] with Al3+ fluorescence system. Its UV-visible absorption spectrum and fluorescence spectrum showed remarkable optical characteristics. The optimal experimental conditions, including reaction temperature, pH, and reaction time were investigated. This system possessed a good anti-interference ability toward the other 16 metal ions. The M1 shows good linearity with Al3+ concentration (1 × 10-6 ~ 15 × 10-6 mol/L). The LOD (Limit of Detection) was 7.55 × 10-8 mol/L. It has good resistance to interference. It was excellently resistant to interferences. The complexation ratio between the M1 probe and Al3+ is 1:1. Furthermore, the binding mechanism was conjectured. We applied the constructed fluorescence system for the first time to the determination of Al3+ in Chinese herbal medicines, and fluorescence imaging in living cells.